Skin disease in wrestling - Lawton, R. (1999)
In recent years, skin disease in wrestling has finally received the attention it deserves. With the NCAA mandating skin inspections prior to each competition, the wrestling community was forced to address the issue. For many years it was a taboo subject, similar to "cutting weight". Many ignored the problem or attempted to cover it up with make-up. Others treated the skin lesion with a variety of home remedies in an attempt to kill it. There was a fear that it would keep the wrestler from competition. Holding one wrestler from competition is better than infecting many. A big factor in these problems was the lack of education among the wrestling and medical community. Physicians, coaches, athletic trainers and wrestlers needed to recognize the signs, symptoms and appearance of various skin diseases. Another problem was identifying the proper treatment for each skin disease. Many of the traditional medications used on the general population were not working effectively with wrestlers. It seemed to be a more resistant strain and more difficult to attack. Recent research and education has greatly improved the diagnosis and treatment of skin disease in wrestling. One person leading the charge has been Dr. David Vasily, Team Dermatologist at Lehigh University in Bethlehem, PA. Along with Jack Foley, Director of Sports Medicine at Lehigh, they have increased awareness of the importance of controlling skin disease in wrestling. They wrote NCAA guidelines and were a big factor in the NCAA mandating skin inspections. They have also developed treatment protocols and continue to try new medications for various skin problems. The two major skin diseases in wrestling are herpes gladiatorum and tinea gladiatorum.